Ekplorasi dan Identifikasi Anggrek Lokal di Desa Sabuhur, Tanah Laut, Kalimantan Selatan: Local Orchids Exploration and Identification in Sabuhur Village, Tanah Laut, South Kalimantan - Istikowati, Wiwin Tyas; Sunardi, Sunardi; Abidin, Zainal; Surya, Adhi; Fauzan, Akhmad; Saputra, Debi Imam; Norhidayah, Anisa; Hadijah, Siti; Sari, Evita; Hidayanti, Nurul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This community services activity aims to support environmental conservation activities by Amabilis Lestari Forest Farmer Group and Pantai Baru Forest Farmer Group in Sabuhur village, Jorong District, Tanah Laut, South Kalimantan. Partners in this program carried out the rescue of local Kalimantan Orchids and ulin wood around the village. The problem is that the kept orchids have not been indicated and inventoried. In this activity, exploration of orchids into their habitat and identification of the types of orchids kept by partners. There are 58 families of orchids maintained by partners with a total of 1.636 plants. Types of orchids are named using a QR-Code attached to the orchids to make it easier to identify the type of orchids. The information contains photos of orchids, identification, habitat, and how to care for them. This service activity can help partners identify all types of orchids that are kept and display them in the form of information that is easily accessible to visitors.